THE EFFECT OF ORGANIZATIONAL SUPPORT, INTERNAL COMMUNICATION AND ORGANIZATIONAL CULTURE ON EMPLOYEES' WORK DISCIPLINE AT HAWARI ESSA HOSPITAL, TEGAL DISTRICT - Dimas Rifqi; Haddan D; Rukhiyat; Kosasih; Vip Paramarta; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
All hospital employees in providing services to patients are required to have high work discipline, but in reality, there are still often problems with the lack of work discipline of hospital employees, especially at Hawari Essa Hospital, Tegal Regency. Factors that are suspected to influence the work discipline of hospital employees are due to organizational support, internal communication and organizational culture. The purpose of this study is to determine the effect of organizational support, internal communication and organizational culture on the work discipline of employees at Hawari Essa Hospital, Tegal Regency. This research method is quantitative research with data analysis techniques namely descriptive analysis. The research instrument uses a Likert scale questionnaire. The sampling technique uses purposive sampling with a sample size technique using Slovin so that the number of samples is 101 respondents. The results of this study are based on the results of the partial t test, it is known that organizational support has a positive and significant influence on employee work discipline, internal communication has a positive and significant influence on employee work discipline and organizational culture has a positive and significant influence on employee work discipline. The results of the simultaneous F test state that organizational support, internal communication and organizational culture simultaneously have a positive and significant influence on employee work discipline. Based on the test results, it means that there is an influence of organizational support, internal communication, and organizational culture on the work discipline of employees at Hawari Essa Hospital, Tegal Regency.